Time bandit : two brothers, the Bering Sea, and one of the world's deadliest jobs - Hillstrand, Andy.; Hillstrand, Johnathan; MacPherson, Malcolm (2008)
Among those who are drawn to risk their lives and seek their fortunes upon the waves, perhaps none take more chances than the men and women who brave the tempestuous, bountiful waters of the Bering Sea. Season after season, they battle with its icy depths, determined to reap yet one more harvest while eluding the ever-present threat of sudden death. If you've watched the exploits of brothers Andy and Johnathan Hillstrand on TV's Deadliest Catch, you've only scratched the surface. To read this book is to step into their skins, smell the sea air, feel the frigid wind, and know with all your senses the exhilarating, and terrifying life on the edge.--From publisher description.
Keywords: Hillstrand, Andy; Hillstrand, Johnathan; Alaskan king crab fisheries -- Bering Sea